A biomimetic urethral model to evaluate urinary catheter lubricity and epithelial micro-trauma. (August 2020) - Humphreys, Owen; Pickering, Mark; O'Cearbhaill, Eoin D.; Flanagan, Thomas C.
Abstract: The standard method of evaluating the lubricity of intermittent urinary catheters with coefficient of friction (CoF) testing is not physiologically relevant, while there is also a dearth of published research on catheter-associated urethral micro-trauma. We developed a novel human urethral epithelial cell-seeded model of the urethra to replace the rubber counter-surface used in standard CoF testing. This cell-seeded model, in conjunction with a novel testing device, allows an investigation of catheter-associated epithelial micro-trauma in vitro for the first time. The CoF of four brands of commercially-available hydrophilic-coated intermittent catheters was measured using both the rubber and urethral model counter-surfaces. Post-catheterisation of the urethral model, the damage to the epithelial layer was analysed using standard cell imaging. The rubber counter-surface was shown to over-estimate the CoF of gel-coated catheters compared to our urethral model due to stick-slip behaviour caused by polymer-on-polymer interaction of the catheter base material on the rubber counter-surface. We identified no deleterious effect due to the presence or design of catheter eyelets to either the CoF measurements or the degree of epithelium damage in our model. Furthermore, the epithelial damage did not correlate with the measured CoF of the low friction catheters, suggesting a more nuanced pathogenesis of urethral irritation and casting doubt on the translatability of a solely mechanical assessment of lubricity of urinary catheters to a clinical effect.